2022
DOI: 10.21203/rs.3.rs-1712072/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence of antenatal depression and associated factors of continuous three trimesters depression: A multicentre study in Chengdu, China

Abstract: Background Antenatal depression (AD) is a major depressive disorder during pregnancy, which may lead to devastating sequelae for the expectant mothers and infants. This study aims to investigate the prevalence of (AD), and to explore influence factors of AD among pregnant women of continuous three trimesters in Chengdu, China. Methods The prospective study included pregnant women who were in their first, second and third trimester pregnancy and were recruited from four maternity hospitals by using the method… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Details of the literature search and screening process are presented in Figure 1. After sufficient screening, 14 studies met criteria and were included in the final analysis [12,17–29] . The main features of the included trials are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Details of the literature search and screening process are presented in Figure 1. After sufficient screening, 14 studies met criteria and were included in the final analysis [12,17–29] . The main features of the included trials are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Utilizing the Jadad score form, the methodological quality of the included trials was assessed, and is shown in Table 2. All 14 studies [12,17–29] received ≥3 points and were included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations